Snoop Doggy: Automatic Robotic Floor Cleaner - Pahadsingh, Sasmita; Mohanty, Roopambika; Kumari, Kalpana; Noor, Sayed Jamal; Satpathy, Priya Chandan (IRO Journal on Sustainable Wireless Systems, 2024)
Due to current technology advancements, researchers have been concentrating more on robots in an attempt to enhance human existence. Home automation and intelligence are growing in today’s houses. People may simplify their lives and save time with home automation. Though the market is still young and developing, domestic robots are finding their way into people’s homes and daily lives. Nonetheless, growth will be needed and the use of domestic robots is changing. The objective is to develop a robotic floor cleaner that uses border analysis to automatically cover a given room or area. The proposed work is named snoop dog as the device will walk in the house like a dog patrolling his territory. The device travels around the room in a zigzag pattern. To cover the whole room, the system detects boundaries using ultrasonic sensors and responds appropriately. In order to collect dust, the device also features a vacuum suction cleaner attached to its rear. Initially, the robot locates a corner and activates the vacuum. After then, it covers the entire region in a zigzag pattern. It functions best in a room free of obstacles, however this problem might be resolved in future enhancement.